Computer science: Subject, fundamental research problems, methodology, structure, and applied problems - Gurevich, I. B.; Zhuravlev, Yu. I. (Pattern recognition and image analysis, 2014)
The work is devoted to computer science. The subject, fundamental research problems, methodology, structure, and applied problems are defined and analyzed. The mathematical apparatus of computer science and its main methods—formalization, algorithmization, mathematical modeling, and programming—are considered. A characterization is given to the main fields of computer science pattern recognition, image analysis, artificial intelligence, intelligent data analysis, and information technologies. An in-depth analysis is carried out of the relationship and interaction between computer science and cybernetics. The role and the subject of informatics are discussed.